Challenging gender equality in South African transformation policies - a case of the White Paper: A programme for the transformation of higher education - Akala, Betty M. (South African Journal of Higher Education, 2018)
Using a post-structural lens, I make arguments against homogenising people’s conditions and circumstances. In particular, I acknowledge that the post-1994 reform agenda intended to streamline the previously fragmented and segregated higher education landscape under the apartheid regime. Black women, who are the main target of this article suffered triple marginalisation ‒ race, social class and sexism. The aim of the article is to show the tensions that exist within the White Paper: A Programme for the Transformation of Higher Education (DoE 1997). The said tensions have stifled the attainment of gender equity and equality; effectively widening the gender fissures in post-1994 South African higher education. I argue that we should not take for granted phrases such as “equal opportunities” and “equal access” in policies. Instead, we should seek their meaning and achievement inter alia in earnest for the targeted group.Therefore, I postulate that gender and gendering is complex and very fragmented. For this reason, formulating transformation interventions on the premise of equality for all does not necessarily guarantee gender equality or gender equity. With this in mind, a “one-size fits all” approach to redressing gender equality is implausible and does not suffice in addressing salient gender injustices. I propose a multifaceted approach, which encompasses a realistic and holistic outlookon the divergent needs of black women in particular and women in general as a possible solution to the current challenges.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; afrique; afrique du sud; approches et analyses; discipline; histoire et politique; patriarcat; post-structuralisme; projet charge mentale; périodes historiques; racisme; ressource en ligne; régions géographiques; science de l'éducation; sexisme; système colonial; systèmes d'oppressions; thématiques; travail; éducation des femmes*

Le racisme est un problème de blancs - Eddo-Lodge, Reni; Mazoyer, Renaud (Éditions Autrement, 2018)
« Quand des Blancs feuillettent un magazine, surfent sur Internet ou zappent à la télévision, il ne leur semble jamais étrange de voir des gens qui leur ressemblent en position d'autorité. Les affirmations positives de la blanchité sont tellement répandues que le Blanc moyen ne les remarque même pas. Etre blanc, c'est être humain ; être blanc, c'est universel. Je ne le sais que trop, car je ne suis pas blanche." Après l'élection de Barack Obama, certains ont proclamé l'avènement d'une société post-raciale. Avec une liberté de ton décapante, Reni Eddo-Lodge montre ici combien nous en sommes loin. Elle analyse les méfaits d'un racisme structurel persistant d'autant plus sournois qu'il avance masqué. Car le racisme va bien au-delà de la discrimination ou de l'injure personnelle. Il imprègne le récit historique, l'imaginaire collectif, les institutions et les entreprises. Pourquoi les Blancs pensent-ils ne pas avoir d'identité raciale? Pourquoi la simple idée d'un James Bond noir fait-elle scandale? Comment une fillette noire en vient-elle à se persuader qu'en grandissant, elle deviendra blanche? Le racisme n'est pas une question de valeur morale, mais d'exercice du pouvoir. Entretenir la légende d'une égalité universelle n'aide en rien. Au contraire. Car, pour déconstruire le racisme, il faut commencer par reconnaître l'étendue du privilège blanc. »-- 4ème de couverture.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; afro-féminisme; approches et analyses; com5170; communication; cours; discipline; europe; féminisme afropéen; histoire et politique; journalisme; premier cycle; privilèges; périodes historiques; racisme; racisme systémique; représentation des femmes* racisées; royaume-uni; régions géographiques; système colonial; systèmes d'oppressions; thématiques; violences